Co‐Producing Interdisciplinary Knowledge and Action for Sustainable Water Governance: Lessons from the Development of a Water Resources Decision Support System in Pernambuco, Brazil. Issue 4 (25th October 2018) - White, Dave D.; Lawless, Krista L.; Vivoni, Enrique R.; Mascaro, Giuseppe; Pahle, Robert; Kumar, Ipsita; Coli, Pedro; Castillo, Raúl Muñoz; Moreda, Fekadu; Asfora, Marcelo
Abstract: One of the most pressing global challenges for sustainable development is freshwater management. Sustainable water governance requires interdisciplinary knowledge about environmental and social processes as well as participatory strategies that bring scientists, managers, policymakers, and other stakeholders together to cooperatively produce knowledge and solutions, promote social learning, and build enduring institutional capacity. Cooperative production of knowledge and action is designed to enhance the likelihood that the findings, models, simulations, and decision support tools developed are scientifically credible, solutions‐oriented, and relevant to management needs and stakeholders' perspectives. To explore how interdisciplinary science and sustainable water management can be co‐developed in practice, the experiences of an international collaboration are drawn on to improve local capacity to manage existing and future water resources efficiently, sustainably, and equitably in the State of Pernambuco in northeastern Brazil. Systems are developed to model and simulate rainfall, reservoir management, and flood forecasting that allow users to create, save, and compare future scenarios. A web‐enabled decision support system is also designed to integrate models to inform water management and climate adaptation. The challenges and lessons learned from this project, the transferability of this approach, and strategies for evaluating the impacts on management decisions and sustainability outcomes are discussed. Abstract : Sustainable water management can be improved when scientists, managers, and stakeholders cooperatively develop useful knowledge. Science's impact on decision‐making and sustainability outcomes can be enhanced by building interdisciplinary teams with scientists and stakeholders, collaboratively framing the problems, cooperatively creating solutions‐focused knowledge, and integrating and applying the knowledge and tools.